Effect of laser‐scan strategy on microstructure and fatigue properties of 316L additively manufactured stainless steel. Issue 1 (3rd October 2022) - Roirand, Hugo; Hor, Anis; Malard, Benoit; Saintier, Nicolas
Abstract: The particular roles of grain morphology and defects, controlled using laser‐scan strategies, on the mechanical properties and the fatigue behavior of 316L stainless steel are investigated. Microstructural characterization and X‐ray tomography analysis was performed to understand the genesis of polycrystalline microstructure and defects. Tensile and fatigue tests were performed to analyze the effect of defect population and microstructural properties on plasticity and damage mechanisms during monotonic and cyclic loading. The effect of the grain‐size and shape and type of defect was carefully investigated to evaluate the mechanisms driving the mechanical behavior under quasi‐static and fatigue loading. It is shown that the laser‐scan strategy determines the anisotropy in the plane perpendicular to the building direction. Moreover, contrary to the existing literature, for 316L obtained by AM, the grain size and shape does not affect the mechanical properties, and LoF defects drive the fatigue life, independent of the defect/grain size ratio.